For Flusser From 3kta. - Macedo, André Rangel (Flusser Studies, 2011)
The article presents information on computer as an industrial machine based on scientific theory and produced by technology. It is stated that all necessary knowledge and skill involved in producing computational experience can't be united in one single person. It is stated that computer programming is a heritage from the logic of Industrial production.